ANALISIS TINGKAT KEPADATAN LALAT DI TEMPAT PENAMPUNGAN SEMENTARA (TPS) KECAMATAN PANDAN KABUPATEN TAPANULI TENGAH TAHUN 2023 - Purba, Bahtera David (Fakultas Kesehatan Masyarakat Institut Kesehatan Deli Husada Delitua, 2024)
This research aimed to determine the difference in fly density levels in garbage shelters, Pandan Elok housing and Toholan Dewantara housing, Pandan District, Central Tapanuli Regency. Fly density is a very important public health problem, because flies can carry bacteria from trash cans and dirty places that they reach into food if the food is open, so flies can cause diarrheal diseases. This research method was quantitative research where techniques in data collection are carried out by analytical observation, and cross secsional methods. The location of this research was conducted at the Pandan Elok housing polling station and Toholan Dewantara housing polling station located in Pandan District, Central Tapanuli Regency, North Sumatra. This research was conducted for 1 month starting from April - May in 2023. With details of field survey 1 week, administration 1 week, data collection 1 week. The result of this research was the difference in the level of fly density in the afternoon and evening at the garbage dump of Pandan Elok Housing with a value of p-value = 0.000. There is a difference in the density of flies in the afternoon and evening at the garbage dump of Toholan Dewantara housing with a p-value = 0.000. There is no difference in the density of flies during the day at the garbage dump of Pandan Elok Housing with the garbage dump of Toholan Dewantara Housing with P- value = 0.306 where the average fly is lower during the day at the garbage dump of Pandan Elok Housing. There is a difference in the density of flies in the afternoon at the garbage dump of Pandan Elok Housing with the garbage dump of Toholan Dewantara Housing with p- value = 0.003 where the density of flies in the afternoon at the garbage dump of Pandan Elok Housing is lower on average. There is a difference in the number of fly density levels at the garbage dump of Pandan Elok Housing with the garbage dump of Toholan Dewantara Housing p-value = 0.008. With a difference = -22.06 which means that flies at the garbage dump of Pandan Elok Housing are smaller on average at 22.06 compared to flies at the garbage dump of Toholan Dewantara housing